EVOLUTIONARY SYNTHESIS BY LEDYARD STEBBINS - V. A. Sokolov (Вавиловский журнал генетики и селекции)
The paper concisely reviews the history of establishment of the idea on evolutionary synthesis involving plant objects and its experimental justification. The roles of S. Navashin, E. Babcock, and G.L. Stebbins in the construction of experimental background for evolutionary synthesis involving botanical material are described. The history of the development of Stebbins’ views of the role of hybridization and polyploidy in plant evolution is considered, as well as his brilliant insight into the role of whole genome duplication in the expansion of variation, which were proven only after the advent of the genomics approach.